What Types of Australian Households are in Housing Affordability Stress?1. Issue 1 (27th March 2015) - Borrowman, Luc; Kazakevitch, Gennadi; Frost, Lionel
Abstract : A residual stress measure, based on the level of disposable income after housing costs have been met, which is then compared to a poverty line or budget standard. The measure is adaptable to different household types Using survey data for 2000‐10, the residual measure and 'after housing' budget standards, we develop an Ordered Probit model to identify the specific factors that predict financial stress, housing stress. Contribute to more effective housing policy and may inform decisions on housing policies that specifically target the type of households that are most vulnerable to housing stress. Types of Australian Households are in Housing Affordability Stress.